A novel approach to treat residual peridevice leakage after left‐atrial appendage closure. Issue 2 (29th April 2013) - Wunderlich, Nina; Wilson, Neil; Sievert, Horst
<x xml:space="preserve">Abstract</x> Left atrial appendage (LAA) device closure has emerged as an alternative treatment to conventional anticoagaluation therapy for the prevention of thromboembolic events in patients with atrial fibrillation. In 8–10% of patients with interventional LAA obliteration, relevant residual flow into the LAA persists due to incomplete seal. We present two cases in whom for the first time two different devices were placed to complete occlusion after residual leak with a first device.© 2013 Wiley Periodicals, Inc.